1)y`=4x³+2/cos²2x y`(0)=0+2/1=2
2)y`=-25(3-5x)^4 y`(1)=-25(3-5)=50
3)y`=(2x+4)e^x²+4x-5 y`(1)=(2+4)e^0=6*1=6
4)y`=1/ctgx * (-1/sin²x)=-1/sinxcosx=-2/sin2x y`(π/4)=-2/sinπ/2=-2/1=-2
5)y`=3x²/2√x³+2
6)y`=2/2√2x+4=1/√2x+4 y`(0)=1/2
7)y`=cosx/2√sinx y`(π/2)=cosπ/2/2√xinπ/2=0
8)y`=-sinx/2√cosx y`(0)=-sin0/2√cos0=0
9)y`=2cos(2x-π/4) y`(π/4)=2cosπ/4=2*√2/2=√2
10)y`=8x/2√4x²+5=4x/√4x²+5 y`(0)=0
11)y`=10x/(5x²+4) y`(0)=0
12)y`=17(3x²-4x)(x³-2x²+3)^16 y`(0)=17*0*3=0
13)y`=3ln2 *2^3x-4 y`(2)=3ln2 *2²=12ln2
14)y`=-3sin(3x+π/4) y`(0)=-3sinπ/4=-3√2/2